Paris Commune, “parties” and “movements” - Machado, Eliel (Pontifícia Universidade Católica de São Paulo, 2011)
Guided by the congruence found in the actions ofthe Communards in 1871 between the objectivethey struggled for (the economic emancipationof work) and the ways in which they organizedthemselves to struggle (direct democracy, antibureaucracy,political-ideological pluralism), thisarticle problematizes the political organization ofthe workers, based on the theoretical contributionsof Marx, Lenin and the intellectuals linked tocontemporary social movements